Campos de experiência na BNCC e suas implicações na construção de um currículo opara a educação infantil - Ghidini, Natália de Almeida (2020)
The present study aims to analyze the potentialities/possibilities of the experience fields in guaranteeing children's learning rights in early childhood education, seeking to answer the following problem: How do the Experience Fields ensure/enable the child's learning and development rights in child education? The methodology, with a qualitative approach, was anchored in bibliographic productions and document analysis, especially in the National Common Curricular Base - (BNCC) and in the Guidelines for early childhood education. The dissertation is structured in five chapters, the first being the introduction and the last the conclusion. In the second chapter, some historical elements of the construction of the concept of childhood and the child as a social actor are reconstructed. The third chapter analyzes the BNCC from the point of view of the Fields of Experience as a basis for the curriculum construction for early childhood education. This chapter also reflects on the curricular organization from the perspective of the Fields of Experience and the rights of learning and development. In the fourth chapter, Dewey’s concept of experience is deepened, as well as the potentialities and challenges for the organization of a curriculum by Fields of Experience as a guarantee of children's learning rights. The study sought in the literature the theoretical basis for analyzing the BNCC - Early Childhood Education - Educação Infantil (EI), as an educational policy, through content analysis of the Fields of Experience. For this, we started from the categories: childhood, experience and learning rights. The foundations of Agostinho (2014), Sarmento (2004, 2008, 2011, 2013, 2015) and Marchi (2010) were used to found the concept of child as a social actor. To deepen the concept of experience, the works of Dewey (1959, 1976, 2002), Abbud (2011) and Aranha (2006) were used. The studies by Finco (2015), Barbosa (2009, 2014, 2015, 2016), Fochi (2015) and Oliveira (2017, 2018, 2019) collaborated for the interpretative approach to the Fields of Experience. With the analysis of the BNCC document for the stage of early childhood education, the survey highlights that the Fields of Experiences provide for the realization of rights (playing, knowing yourself, participating, expressing, exploring, living together) by the early childhood school when: a) the child participates in the construction of pedagogical projects; b) there is the understanding of the principle of experience that is in the relationships made through the concept of interaction, playfulness and continuity; c) there is continuous and quality training for professionals in early childhood education; e) there is teacher's intentionality. The survey showed that the BNCC-EI presents an orientation to the proposals of early childhood education that, conditioned to the understanding of childhood, experience and a curriculum articulated with the potentialities of the school's daily life, can guarantee the rights of young children.